2017
DOI: 10.1159/000480002
|View full text |Cite
|
Sign up to set email alerts
|

Acute Intravenous Infusion of Immunoglobulins Protects Against Myocardial Ischemia-Reperfusion Injury Through Inhibition of Caspase-3

Abstract: Background/Aims: To investigate the cardioprotective effects of intravenous immunoglobulins (IVIG) in rats subjected to regional myocardial ischemia reperfusion (I/R). Methods: Langendorff-perfused rat hearts were used in this study. Hearts subjected to regional ischemia served as a negative untreated control. The effects of IVIG pre- and post-ischemic treatment on left ventricular function, coronary vascular dynamics and contractility were assessed. IVIG were administered in either a low or high dose. The inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Casp3 is involved in differentiation of cells [26,27] and elimination of synapses, thus its downregulation might be the mechanism involved in adaptation on ischemia needed for cell survival. Indeed, there is a growing list of evidences that decreased activity of Casp3 is an important mechanism involved in protection against ischemia [28,29]. Further analyses will be needed to understand molecular pathways behind observed increase of expression of Casp3 in the brain affected by ischemia and decreased expression of Casp3 in the transplanted neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Casp3 is involved in differentiation of cells [26,27] and elimination of synapses, thus its downregulation might be the mechanism involved in adaptation on ischemia needed for cell survival. Indeed, there is a growing list of evidences that decreased activity of Casp3 is an important mechanism involved in protection against ischemia [28,29]. Further analyses will be needed to understand molecular pathways behind observed increase of expression of Casp3 in the brain affected by ischemia and decreased expression of Casp3 in the transplanted neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis by Bice et al [121], NO interventions also limited infarct size during the early reperfusion period. In myocardial injury, inhaled gaseous NO inhibited cardiomyocyte apoptosis and reduced infarct size [122-125]. The concentration of creatine kinase also decreased [122-124, 126, 127].…”
Section: Nitric Oxide Corresponding Protection Strategymentioning
confidence: 99%
“…Four types of cardiac dysfunction occurred after myocardial ischemia reperfusion injury, including reflux, myocardial stunning, fatal reperfusion injury and reperfusion arrhythmia (7,8). At present, there are different explanations for the mechanism of myocardial ischemia-reperfusion injury, such as oxygen free radical theory (9), calcium overload theory (10) and inflammatory response theory (11). Kocak et al (12) suggested that apoptosis would occur during myocardial ischemia-reperfusion injury, and apoptosis plays a decisive role in the final infarct area of myocardium.…”
Section: Discussionmentioning
confidence: 99%